Perlindungan Hukum Investor Atas Fenomena Gagal Serah Efek: Dari Perspektif PT KPEI - mialdy, Maharani putri; Suryanti, Anggi Aprilia Suryanti; Oktavia, Nur; Azmi, Zul (CV. ITTC INDONESIA, 2023)
This study aims to find out the form of legal protection for Indonesian investors in the practice of Repurchase Agreement (Repo) if there is a failure in filing for securities from PT KPEI's point of view. The Repo system with collateral in the form of securities opens up new opportunities for investors to invest safely and profitably. However, this can lead to new problems such as legal exemption for events that fail to deliver securities. This research is a qualitative descriptive study with data analysis methods based on literature review originating from previous research. According to various sources studied, if there is a failure in the submission of shares, the Repo system has provided legal protection through procedures to deal with failure events that are adjusted to the rights and obligations of investors in the form of written compensation. Besides that, obtaining information regarding Tri-party Repo can also provide investors with more legal protection. PT KPEI also provides another alternative to finalize the agreement in the form of a securities lending and borrowing facility to create a fair, orderly and efficient capital market.